ULBP1 Is Elevated in Human Hepatocellular Carcinoma and Predicts Outcome - Easom, Nicholas J. W.; Marks, Michael; Jobe, Dawda; Gillmore, Roopinder; Meyer, Tim; Maini, Mala K.; Njie, Ramou (Frontiers in Oncology, 2020)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer death worldwide, and despite recent immunotherapeutic advances there remains a need for improved diagnostic, prognostic, and therapeutic tools. UL-16 binding protein 1 (ULBP1) is a ligand of the activatory receptor Natural Killer cell Group 2 receptor D (NKG2D) and is found as a cell-surface protein on some malignant cells including on human hepatocellular carcinomas. We aimed to explore the biological and clinical significance of NKG2D ligands in the circulation of patients with HCC. We measured ULBP1 in the serum of two retrospective cohorts of patients with HCC from the PROLIFICA cohort in The Gambia (n = 43) and from a tertiary care setting in the UK (n = 72) by sandwich ELISA. Exosome isolation by size exclusion was used to compare ULBP1 concentration in exosomes and as free protein. Survival analysis was performed and multiple linear regression and Poisson regression were used to assess the independent effect of ULBP1 concentration. ULBP1 was raised in both cohorts with HCC regardless of the underlying liver disease, and was not associated with markers of cirrhosis such as platelet count or serum albumin. ULBP1 was present predominantly as free protein rather than bound to exosomes. Serum ULBP1 > 2000 pg/ml was associated with a significantly reduced survival in both cohorts (hazard ratios in Gambian and UK cohorts 2.37 and 2.1, respectively). The effect remained significant after adjustment for BCLC staging (p = 0.03). These data suggest that ULBP1 merits further investigation as a prognostic marker in HCC in diverse settings and should also be explored as a therapeutic target.